Hubungan antara Profil Lipid dengan Kejadian Retinopati Diabetika pada Pasien Diabetes Melitus Tipe 2 di Fasilitas Kesehatan Tingkat Pertama Klinik Tanjung Purwokerto - Harini, Ika Murti; Setyanto, Muhamad Rifqy; Gumilas, Nur Signa Aini; Ernawati, Dwi Arini (Faculty of Medicine, Universitas Andalas, 2022)
Diabetic retinopathy is a major microvascular complication due to diabetes mellitus (DM) and prolonged hyperglycemia. One of the risk factors for the development and progression of diabetic retinopathy is lipid profile levels in DM patients. Objectives: To determined the relationship between lipid profile and the incidence of diabetic retinopathy in DM patients who follow the Chronic Disease Management Program at the Â first level health facilities Klinik Tanjung Purwokerto. Methods: The number of respondents in this study was 49 people. The independent variables assessed were lipid profiles, including levels of total cholesterol, triglycerides, LDL, and HDL. The dependent variable is the incidence of diabetic retinopathy determined by an ophthalmologist. Statistical analysis to determine the relationship between lipid profile and the incidence of diabetic retinopathy used the Chi-square test and calculated the odds ratio (OR). Results: The results showed that there was no relationship between levels of total cholesterol (p=0.586), triglycerides (p=1), and LDL (0.719) with the incidence of diabetic retinopathy. The statistical analysis results of the relationship between HDL levels and the incidence of diabetic retinopathy were known to have a p-value = 0.046 (OR 4.83; 95% CI 1.23-18.98). Conclusion: There is a significant relationship between HDL levels and the incidence of diabetic retinopathy in Type 2 DM patients at the FKTP Klinik Tanjung Purwokerto. DM patients with abnormal HDL levels are 4.83 times more likely to develop diabetic retinopathy than DM patients whose HDL levels are normal.Keywords: diabetes mellitus, Â lipid profile, diabetic retinopathy